2013
DOI: 10.4062/biomolther.2013.026
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 as a New Potential Biomarker for Cisplatin-Induced Toxicity in Human Kidney Epithelial Cells

Abstract: Cisplatin is a member of platinum-containing anti-cancer drugs that causes cross-linking of DNA and ultimately cancer cell apoptosis. The therapeutic function of cisplatin on various types of cancers has been widely reported but the side effects have been discovered together and nephrotoxicity has been regarded as major side effect of cisplatin. To select candidates for new sensitive nephrotoxicity biomarker, we performed proteomic analysis using 2-DE/MALDI-TOF-MS followed by cisplatin treatment in human kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…HEK 293 cells were transfected transiently or stably with 10 g of plasmid construct by lipofectamine 2000 (Kim et al, 2003). The cells cultured at 37 • C and 5% CO 2 in Dulbecco's modified Eagle's medium supplemented with 10% heat-inactivated fatal bovine serum (FBS) in the presence of 0.5 mg/ml G418, 50 U/ml penicillin and 50 g/ml streptomycin (Kwon et al, 2013).…”
Section: Expression Of Pspam1 In Hek 293 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEK 293 cells were transfected transiently or stably with 10 g of plasmid construct by lipofectamine 2000 (Kim et al, 2003). The cells cultured at 37 • C and 5% CO 2 in Dulbecco's modified Eagle's medium supplemented with 10% heat-inactivated fatal bovine serum (FBS) in the presence of 0.5 mg/ml G418, 50 U/ml penicillin and 50 g/ml streptomycin (Kwon et al, 2013).…”
Section: Expression Of Pspam1 In Hek 293 Cellsmentioning
confidence: 99%
“…Pig sperm and HEK293 cells were chilled on ice for 2 h and subjected to a lysis buffer consisting of 20 mM Tris-HCl, pH 7.4, 1% Triton X-100 (TX-100), 150 mM NaCl, and 1% protease inhibitor cocktail (Sigma-Aldrich) for the extraction of proteins (Kwon et al, 2013). After centrifugation at 10,000 × g for 10 min at 4 • C, proteins retained in the supernatant were analyzed.…”
Section: Preparation Of Protein Extractsmentioning
confidence: 99%
“…Previously, it was reported that annexin A5 plays an important role in cisplatininduced mitochondria-dependent apoptosis in renal cells (Jeong et al, 2014;Kwon et al, 2013). To determine whether annexin A5 participated in auranofin-induced mitochondriadependent apoptosis, changes in annexin A5 mRNA and protein expression were measured.…”
Section: Auranofin Induces Expression Of Annexin A5 and Translocationmentioning
confidence: 99%
“…Recently, data demonstrated that annexin A5 plays an important role in cisplatin-induced toxicity by mediating the mitochondrial apoptotic pathway via the induction and oligomerization of the voltage-dependent anion channel (VDAC) (Jeong et al, 2014;Kwon et al, 2013). Cisplatin is a well-known gold compound that induces mitochondria-dependent apoptosis (Xiao et al, 2003;Kim and Moon, 2012;Carvalho Rodrigues et al, 2012).…”
mentioning
confidence: 99%
“…A standard treatment for late stage NSCLC is cisplatin (cis-diamminedichloroplatinum (II)) in combination with another drug, such as paclitaxel or docetaxel [2][3][4]. Because cisplatin is a non-specific anticancer drug, its therapeutic use is associated with significant off-target side effects, including nephrotoxicity [5]. Furthermore, taxanes and vincas, which are commonly used in combination with cisplatin, are neurotoxic [6].…”
Section: Introductionmentioning
confidence: 99%